1993
DOI: 10.1111/j.1365-2621.1993.tb04328.x
|View full text |Cite
|
Sign up to set email alerts
|

Soybean Flour Lipoxygenase lsozyme Mutant Effects on Bread Dough Volatiles

Abstract: Lipoxygenases are implicated in improvement of bread quality after addition of enzyme active soy flour. However, differences among the three major isozymes in soybeans in terms of impact on bread characteristics are not known. Differences exist among soybean lipoxygenase isozymes in terms of stability and generation of volatile flavor and aroma. Soybean flour with different lipoxygenase isozymes present might affect bread dough volatiles or defatting may affect activity of the isozymes. Full fat or defatted so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
3

Year Published

1994
1994
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 13 publications
0
18
0
3
Order By: Relevance
“…LOX is considered an oxidative improving agent, because the products formed during the oxidation of flour fatty acids have a cross‐linking effect on the flour proteins by oxidation of the glutenin thiol groups (Faubion and Hoseney ; Addo and others ; Permyakova and Trufanov ). As such, the use of LOX, in the form of enzyme‐active soybean flour, as dough improver is commonplace during the production of white bread (Faubion and Hoseney ; Luning and others ).…”
Section: Lox In the Baking Industrymentioning
confidence: 99%
See 2 more Smart Citations
“…LOX is considered an oxidative improving agent, because the products formed during the oxidation of flour fatty acids have a cross‐linking effect on the flour proteins by oxidation of the glutenin thiol groups (Faubion and Hoseney ; Addo and others ; Permyakova and Trufanov ). As such, the use of LOX, in the form of enzyme‐active soybean flour, as dough improver is commonplace during the production of white bread (Faubion and Hoseney ; Luning and others ).…”
Section: Lox In the Baking Industrymentioning
confidence: 99%
“…Lipoxygenase (linoleate: oxidoreductase, EC 1.13.11.12, LOX) is a group of non‐heme metal‐containing dioxygenases which catalyze the regio‐ and stereo‐specific dioxygenation of polyunsaturated fatty acids to conjugated unsaturated fatty acid hydroperoxides (Faubion and Hoseney ; Addo and others ; Robinson and others ; Brash ; Liavonchanka and Feussner ; Baysal and Demirdoven ; Permyakova and Trufanov ). Although these enzymes are widely distributed in the animal and plant kingdoms, they are particularly abundant in grain legume seeds and potato tubers (Axelrod ; Faubion and Hoseney ; Robinson and others ; Casey and others ; Baysal and Demirdoven ; Miguel and others ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been found that the concentrations of hexanal, hexanol, l-penten-3 -ol, 1-pentanol and 2-heptanone are increased upon the addition of soya flour (Luning et al 1991, Addo et al 1993. Fatty acids are oxidized for the production of "green" flavor components, the so-called "leaf aldehydes" and "leaf alcohols", which may be obtained enzymatically through lipoxygenase and hydroperoxide lyase.…”
Section: Fatsmentioning
confidence: 98%
“…The enzyme lipoxygenase can be found in legumes such as soybeans, peas, peanuts, mung beans, and navy beans, and can have negative effects on the colour, flavour, texture, and nutritional nutritive properties of foods (Addo et al 1993). Development of off-flavour in legume products is highly dependent on the action of the various endogenous lipoxygenases, since subsequent decomposition of the resulting hydroperoxides produces a rancid flavour.…”
Section: Introductionmentioning
confidence: 99%